Robert B. Parker's Ironhorse [compact disc, unabridged] - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Cole and Hitch novel., 2013)
"Virgil Cole and Everett Hitch, newly appointed as Territorial Marshals, find themselves traveling by train through Indian Territories. Their first marshaling duty starts as a simple prisoner escort mission, but becomes complicated when the Texas Governor and his family board the train--along with $500,000. The men have to watch for and contend with Bloody Bob Brandice, who was left with two .44 slugs in his chest during his last meeting with Virgil"--